Wideband and UWB Antennas for Wireless Applications: A Comprehensive Review - Renato Cicchetti; Emanuela Miozzi; Orlandino Testa (International Journal of Antennas and Propagation)
A comprehensive review concerning the geometry, the manufacturing technologies, the materials, and the numerical techniques, adopted for the analysis and design of wideband and ultrawideband (UWB) antennas for wireless applications, is presented. Planar, printed, dielectric, and wearable antennas, achievable on laminate (rigid and flexible), and textile dielectric substrates are taken into account. The performances of small, low-profile, and dielectric resonator antennas are illustrated paying particular attention to the application areas concerning portable devices (mobile phones, tablets, glasses, laptops, wearable computers, etc.) and radio base stations. This information provides a guidance to the selection of the different antenna geometries in terms of bandwidth, gain, field polarization, time-domain response, dimensions, and materials useful for their realization and integration in modern communication systems.